2015
DOI: 10.7863/ultra.15.03076
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quasistatic Ultrasound Elastography for Examination of Scrotal Lesions

Abstract: Quasistatic elastography can reflect the relative stiffness of the testis and its surrounding tissues, thus providing a novel, reliable, convenient, and noninvasive method for clinical detection of testicular stiffness and related pathologic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…1). This is known as a 3-ring structure [7]. Mean shear wave velocities of 0.76 m/sec (95% confidence interval, 0.75 to 0.78 m/sec) from 130 normal testicles and 1.92 m/sec in 19 patients with testicular cancer have been reported by Pedersen et al [8] and Marcon et al [9], respectively, both using virtual touch tissue imaging quantification (VTIQ; Siemens Medical Solutions, Mountain View, CA, USA).…”
Section: Normal Testesmentioning
confidence: 99%
“…1). This is known as a 3-ring structure [7]. Mean shear wave velocities of 0.76 m/sec (95% confidence interval, 0.75 to 0.78 m/sec) from 130 normal testicles and 1.92 m/sec in 19 patients with testicular cancer have been reported by Pedersen et al [8] and Marcon et al [9], respectively, both using virtual touch tissue imaging quantification (VTIQ; Siemens Medical Solutions, Mountain View, CA, USA).…”
Section: Normal Testesmentioning
confidence: 99%
“…They found that stiffness increased and volume decreased as age increased. Following this study, testicular elastography was used to examine various types of testicular focal lesions, torsion or segmental infarctions [13,[18][19][20][21][22][23][24]. These studies demonstrated the feasibility of elastography for evaluating elasticity in normal and diseased testes.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound equipment with elastographic options can more accurately image and evaluate the properties of lesions located in many organs, such as the breast, thyroid, testis, prostate, lymph nodes, and brain tissue. 3,[18][19][20][21][22][23] The progress of US elastography applied to brain tissue is reviewed below.…”
Section: Application Progressmentioning
confidence: 99%